А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid - Sinev, Artem Y.; López-Blanco, Charo (Zootaxa, 2018)
A new species of Cladocera, Alona begoniae sp. nov. (Anomopoda: Chydoridae) was found in ancient Lake Ohrid. Its habitus and outer morphology is similar to one of the most common Palearctic species, Coronatella rectangula (Sars, 1862), and this can be the main reason why it has remained undiscovered. A. begoniae sp. nov. belongs to the elegans-group of Alona s. lato, a relict genus-level group not formally recognised yet as a separate taxonomical unit. Its habitat appears to be sandy and stony substrates (at 2–12 m depth) bare of vegetation. The position of this new species within the Alona-like anomopods is evaluated and similarities with other cladocerans in ancient lakes are discussed.